Dissolution behaviour of Al2O3 in mould fluxes with low SiO2 content. Issue 3 (15th February 2019) - Li, Zhirong; Jia, Boran; Zhang, Yabing; He, Shengping; Wang, Qiangqiang; Wang, Qian
Abstract: A kinetic model of the dissolution of Al2 O3 into mould fluxes with low SiO2 content was established, and the restrictive step of the dissolution process was investigated by employing a rotating cylinder method. Then, the effects of the relative moving speed between the Al2 O3 sample and the flux as well as the effects of the temperature and composition on the dissolution rate of Al2 O3 were analysed. The results showed that the dissolution of Al2 O3 is controlled by the diffusion in the product layer. The dissolution rate increases with the increase in the relative moving speed and temperature. The activation energy of the dissolution of Al2 O3 into mould fluxes A-1, A-2, and B were 150.8 kJ mol −1, 156.1 kJ mol −1, and 131.4 kJ mol −1, respectively. The dissolution accelerates with increasing (CaO+BaO)/(Al2 O3 +SiO2 ) ratio and Na2 O, Li2 O, B2 O3, and F − contents. The result of the analysis of the Al2 O3 /flux interface by scanning electron microscopy–energy dispersive X-ray spectroscopy showed that a product layer was formed in the dissolution process, with interfacial products BaO·6Al2 O3 and BaO·2CaO·4Al2 O3 .